(untitled) (Eurasian Research Bulletin, 2023)
Gastrointestinal bleeding is a relatively common and serious form of gastrointestinal hemorrhage. It can be precisely defined as bleeding within the intestinal tract, originating from the ligament of Treitz. In Western countries, it tends to be more prevalent in men than in women. Potential causes include peptic ulcer disease (PUD), gastric arteriovenous malformation, Mallory-Weiss tears, aortoenteric fistula, and malignancies like squamous cell carcinoma (SCC). This type of bleeding accounts for approximately 75% of all cases and necessitates meticulous diagnostic and treatment approaches. The risk of rebleeding should be evaluated using scoring systems such as Rockall and Blatchford scoring. Effective diagnosis and treatment strategies heavily rely on the expertise of professionals in interventional radiology, internal medicine, emergency medicine, gastroenterology, and general surgery. In this study, we emphasize that the diagnosis and treatment strategies are critically dependent on the collaboration of experts in interventional radiology, internal medicine, emergency medicine, gastroenterology, and general surgery. This review article aims to provide a concise overview of diagnostic procedures and treatment approaches, offering valuable guidance to physicians and clinical practitioners for the effective management of gastrointestinal bleeding patients